If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12y + -6 = 0 Reorder the terms: -6 + 12y = 0 Solving -6 + 12y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 12y = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 12y = 0 + 6 12y = 0 + 6 Combine like terms: 0 + 6 = 6 12y = 6 Divide each side by '12'. y = 0.5 Simplifying y = 0.5
| 6x-3-5x=3 | | -ax+3bx=-10 | | 3+3x=-2x+43 | | 20m=60 | | y^2=36+x^2 | | 18p=-306 | | 3y-y^2=3 | | 49x+14x+1=0 | | 8+5x-4x=13 | | 2b-90=90 | | xy-6x+2y=12 | | cos^2x+2cosx-1=0 | | -2(7x-9)=-14x+18 | | 8x-4x+132=8x+48 | | -3(2t-5)=3 | | 1.5+x=7.5 | | 3(x-4)=63 | | sqrt(n)*(4+6n)= | | -55=3x+6x+8 | | 6.7x-3.8=16.3 | | 5(3z-1)-3(z+7)=7(z+1) | | 20s=-140 | | 17-13d=-11d-19 | | 6b-(2b+8)=-16 | | 6x-11=2(5x-30)+9 | | 3+4(x-8)=9-8(8-5) | | 21+28m=28+21m | | x+11=2x-4 | | q+12=-2 | | x^3y^2-x^4y+4xy^3=0 | | 2x+3=59 | | 5=5x-6x-5 |